NMR spectra of chiral olefin (E)-1-benzyliden-2,3,4R(S),5R(S)-tetrabenzylcyclopenta-2-en in the presence of a chiral lanthanide shift reagent and silver auxiliary compound. - Khanh, Pham Ngoc; Kinh, Chu Dinh; Thuy, Thanh Thi Thu; Adolf, Zschunke (Vietnam Journal of Chemistry, 2012)
The chiral olefin (E)-1-Benzyliden-2, 3, 4R(S), 5R(S)-tetrabenzylcyclopenta-2-en was studied by NMR method in the presence of chiral lanthanide shift reagent Ytterbium(III)[tris[3-(heptafluoropropylhydroxymethylene)-l-camphorate]  and the auxiliary silver compound (4,4,4-trifluoro-1-(2-thienyl)-1,3-butanedion) silver(I) in order to find out the effectiveness of this combination on the enantiomeric resolution in NMR-spectrum.